Psychological interventions in psychodermatological practice - Ettappurath N Abdul Latheef; Bishrul N A Hafi (Wolters Kluwer Medknow Publications, 2023)
There is a well-established connection between the skin and the mind. Based on current evidence, many dermatological conditions are triggered or exacerbated by stress. Therefore, intervention needs to target stress, anxiety, and other psychiatric comorbidities which may be secondary to skin conditions or may lead to aggravation of the illness. Psychological interventions should be based on the underlying emotional issues that may affect the way skin problems respond to medical treatment. Before starting the intervention, it is very important to know which psychodermatological conditions will be targeted. In primary psychocutaneous illness (delusion of parasitosis, obsessive-compulsive disorder, dysmorphophobia, etc.) the target is to modify or eliminate the symptoms of illness with specific models and approaches. If stress is playing an active role in the etiology and course of skin conditions (e.g., psoriasis, atopic dermatitis, and urticaria) or it is delaying the improvement, then the aim should be to apply stress reduction techniques. In some skin conditions (pemphigus vulgaris, Hansen's disease, etc.), the aim of the intervention should be to strengthen the defenses and teach new and better mechanisms to maintain control. The common psychotherapy procedures useful in dermatology practice include psychoeducation, behavior therapy, habit reversal, relaxation procedures, biofeedback, cognitive behavior therapy, hypnotherapy, and group therapy.